Penggunaan Bahasa Gaul pada Staf Anggota Marching Gita Cilegon Mandiri dalam Eksistensi Bahasa Indonesia - Mashadi Purnama Saputra; Desma Yuliadi Saputra; Rina Andriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This research is motivated by the phenomenon of the widespread use of slang among teenagers, specifically among the staff members of the Gita Cilegon Mandiri Marching Band. This study aims to: 1) determine the forms of slang use among staff members and 2) determine the factors that influence the use of slang in the presence of Indonesian among staff members. The method used in this study is descriptive qualitative. Data collection techniques include field research, semi-structured interviews and direct or covert observations. The subjects of this study were 14 staff members of the Gita Cilegon Mandiri Marching Band, including 7 female members and 7 male members. The results of the study indicate: 1) slang among staff members of the Gita Cilegon Mandiri Marching Band is something they commonly use in everyday communication, both with peers and within their environment, and 2) the use of slang among staff members of the Gita Cilegon Mandiri Marching Band influences the presence of Indonesian, resulting in a lack of familiarity with standard Indonesian and members' lack of understanding of proper spelling.